2004
DOI: 10.1007/s00420-004-0511-8
|View full text |Cite
|
Sign up to set email alerts
|

Visual evoked potentials in workers with chronic solvent encephalopathy

Abstract: Objectives: Two promising variations of visual evoked potentials (VEPs) were studied in solvent-exposed workers: the effect of a low-contrast stimulus in comparison with the usually applied high contrast, and the ability of pattern-onset VEP to reveal damage to specific visual cortical areas. In addition, we studied disturbances of a visual event-related potential (P300). Methods: Thirty male patients (48±9 years of age) with solvent-induced chronic encephalopathy, and 41 controls (46±8 years) without solvent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
1
0
1
Order By: Relevance
“…Various studies of the eVects of occupational factors on central nervous system (CNS) function using event-related potential (ERP) recording have been performed, in clinical cases of exposure to organic solvents (Morrow et al 1992;Chuwers et al 1995;Lindgren et al 1997;Verberk et al 2004) or hydrogen sulphide (Wasch et al 1989;Hirsch 2002), vibration syndrome (VS) (Hirata et al 1995), surveys on lead exposure Murata et al 1993;Hirata et al 2004), survey on manganese exposure (Wennberg et al 1991(Wennberg et al , 1992 survey on solvent exposure (Estrin et al 1990;Lundberg et al 1995;Vrca et al 1997;Morrow et al 1998), shift work (Yasukouchi et al 1995), vibroacoustic disorder (Martinho andCastelo 1999), and cervico-brachial disorders . Hirata et al (1995) reported that the P300 latencies of vibration syndrome (VS) patients were delayed compared with those of healthy control subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies of the eVects of occupational factors on central nervous system (CNS) function using event-related potential (ERP) recording have been performed, in clinical cases of exposure to organic solvents (Morrow et al 1992;Chuwers et al 1995;Lindgren et al 1997;Verberk et al 2004) or hydrogen sulphide (Wasch et al 1989;Hirsch 2002), vibration syndrome (VS) (Hirata et al 1995), surveys on lead exposure Murata et al 1993;Hirata et al 2004), survey on manganese exposure (Wennberg et al 1991(Wennberg et al , 1992 survey on solvent exposure (Estrin et al 1990;Lundberg et al 1995;Vrca et al 1997;Morrow et al 1998), shift work (Yasukouchi et al 1995), vibroacoustic disorder (Martinho andCastelo 1999), and cervico-brachial disorders . Hirata et al (1995) reported that the P300 latencies of vibration syndrome (VS) patients were delayed compared with those of healthy control subjects.…”
Section: Introductionmentioning
confidence: 99%
“…, 1999;GONG et aI. , 2003;SEEBER et aI., 2004 (MORATA et aL, 1993;MORATA et aL, 1997;THUOMAS et aL, 1996;VRCA et aL,1997;NIKLASSON et aL, 1998;MOEN et aL, 1999 (NYLEN e HAGMAN, 1994;LAUKLI e HANSEN 1995;SLlWINSKA-KOWALSKA, et aL, 2005; (MORROW et ai, 1998;MOEN et aL, 1999;VERBERK et aL, 2004;SEEBER et aL, 2004). Embora pesquisas tenham indicado que algumas dessas habilidades possam estar comprometidas também pela exposição isolada a ruído (COSTA et aL, 1992), neste estudo as repercussões da exposição a solventes sobre a função auditiva central medidas pelo teste do PEALL-P300 foram bem mais evidentes em relação à exposição a ruído.…”
Section: (J)iscussãounclassified